Nomogram for predicting live birth in ovulatory women undergoing frozen-thawed embryo transfer - Ying Wang; Shan Dong; Hengfei Li; Yang Yang; An-Liang Guo; Lan Chao (BMC, 2024)
Abstract Background Study objectives included the development of a practical nomogram for predicting live birth following frozen-thawed embryo transfers in ovulatory women. Methods Totally, 2884 patients with regular menstrual cycles in our center were retrospectively enrolled. In an 8:2 ratio, we randomly assigned patients to training and validation cohorts. Then we identified risk factors by multivariate logistic regression and constructed nomogram. Finally, receiver operating characteristic curve analysis, calibration curve and decision curve analysis were performed to assess the calibration and discriminative ability of the nomogram. Results We identified five variables which were related to live birth, including age, anti-Müllerian hormone (AMH), protocol of frozen-thawed embryo transfer (FET), stage of embryos and amount of high-quality embryos. We then constructed nomograms that predict the probabilities of live birth by using those five parameters. Receiver operating characteristic curve analysis (ROC) showed that the area under the curve (AUC) for live birth was 0.666 (95% CI: 0.644-0.688) in the training cohort. The AUC in the subsequent validation cohorts was 0.669 (95% CI, 0.625-0.713). The clinical practicability of this nomogram was demonstrated through calibration curve analysis and decision curve analysis. Conclusions Our nomogram provides a visual and simple tool in predicting live birth in ovulatory women who received FET. It could also provide advice and guidance for physicians and patients on decision-making during the FET procedure.